Median based approaches for noise suppression and interest point detection. - Miao, Zhenwei. (2013)
Mean and median are two basic operations in signal/image processing. They are widely used for their easy implementation and soundly mathematical analysis tools. The mean filter achieves the best performance in attenuating Gaussian noise. However, it cannot effectively suppress the long-tailed noise and it blurs image structures. On the contrary, the median filter has the advantages in suppressing the long-tailed noise and preserving image structures. These advantages motivate us to develop the median based approaches in both noise suppression and interest point detection.